Veering right : how the Bush administration subverts the law for conservative causes - Tiefer, Charles (University of California Press, 2004)
In this searing indictment of current administration policy, Charles Tiefer, a distinguished scholar of national legal affairs and former solicitor of the House of Representatives, argues that President George W. Bush methodically manipulates the law to promote right-wing causes. The beneficiaries of these machinations range from frontline pro-weapon and anti-women's rights groups to major industries that profit from lax environmental standards and military intervention in resource-rich regions. Accessibly written, legally rigorous, and meticulously documented, Veering Right demonstrates how t.